Civil Servants' Interpretation of Gold Investment and Trading (Case Study of Civil Servants in South Sulawesi Province) - Dinah Diyanah Burhan; Alimuddin; Darwis Said (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the interpretations, behaviors, and preferences of gold investment among civil servants (PNS) of the South Sulawesi Provincial Government in facing economic volatility and inflation. Using a descriptive qualitative method with a case study approach, this study collected data through in-depth interviews with 13 informants consisting of active civil servants, retirees, and financial practitioners, supported by secondary data analysis. The results show that PNS interpretations of gold are multidimensional, namely as an effective life buffer and hedge against inflation, as well as an instrument for fulfilling cultural obligations (uang panai' and siri'). This study found a transformation in investment behavior from gold jewelry to gold bars and digital savings, driven by mental accounting mechanisms through payroll deduction systems to discipline spending. In conclusion, the local culture of Bugis-Makassar interacts dynamically with modern financial literacy, creating a hybrid investment pattern supported by sharia compliance and the integration of regional banking technology.